(untitled) (Archaeologia Adriatica, 2010)
The site of Pakoštane-Crkvina, situated at the position called Košević at the west coast of the Vrana Lake, in the immediate vicinity of the road connecting Pakoštane and Vrana, has been systematically excavated by the Department of Archaeology of the University of Zadar. On this occasion the authors selected numismatic finds which were recovered during the last five research campaigns out of multitude of archaeological objects. Total of 11 coins were found so far, covering wide chronological range from the 4th to 18th centuries. Numismatic finds from the site of Pakoštane – Crkvina were poorly preserved. However after cleaning and conservation it was possible to determine with certainty dating of ten preserved numismatic finds. This numismatic material represents a reflection of historical-commercial activities of the wider Mediterranean region, including the city of Zadar and its wider surrounding which comprises the site of Pakoštane-Crkvina as its inseparable part.